A Cumulative Expansion Force-Finding Method for Suspension-Cable Truss Composite Structure - Lifan Huang; Bin Luo; Mingmin Ding; Chunshui Zhang; Yangjie Ruan (Advances in Civil Engineering)
Suspension-cable truss composite structure is a new type of cable-strut structure which combines the conventional cable structure with the rigid truss. By laying rigid roofing slabs, this composite structure offsets most effect of the wind suction, reduces the axial force of the stable cables, and reduces the large vertical displacement effectively when compared with conventional cable trusses. For this new structure, the deformation relevance between adjacent substructures results in a nonindependent and stable union. To effectively and precisely find the cable forces of a suspension-cable truss composite structure for the construction completion state, a proper optimization order and a suitable selection of the substructures are necessary. In this paper, the structural mechanical characteristics of the suspension-cable truss composite structure are introduced at first, to reveal the force transmission path between adjacent substructures. Secondly, the cumulative expansion force-finding method (CEFM) is proposed to obtain the optimal mode of the cable force distribution with a suitable operational efficiency. A numerical example is introduced and analyzed to verify the accuracy and feasibility of this method afterwards. The results show that CEFM could find out the optimal cable force distribution of the suspension-cable truss composite structure, with a geometry shape of whole structure and a rational stress level of all the components.